Job profile and infection control of dental assistants in Tehran, Iran - Ghasemi, Hadi; Jadidfard, MohammadPooyan; Alirezaee , Kazem (Journal of Dental School, 2023)
Objectives: This study aimed to investigate background and job characteristics of dental assistants in Iran and to assess their knowledge and practice about infection control. Methods: This cross-sectional study conducted on a sample of dental assistants in Tehran. The participants answered an online questionnaire including demographic (age, gender, marital status, and the highest educational attainment) and job related (years in practice, income, working hours, job related educational course and certificate, knowledge and practice regarding infection control) questions. Objectives This study aimed to investigate the background characteristics and job profile of dental assistants in Iran and to assess their knowledge and practice regarding infection control. Methods This cross-sectional study was conducted on a sample of dental assistants in Tehran, Iran. The participants completed an online questionnaire, including demographic (age, sex, marital status, and the highest level of educational attainment) and job-related (years of practice, income, working hours, job-related educational course and certificate, and knowledge and practice related to infection control) information. Results A total of 386 dental assistants completed the questionnaires. The mean age of the assistants was 29.27±6.8 years, and 96% of them were female. Overall, 56-68% of the respondents reported <5 years of working experience, worked 30-80 hours per week with a monthly salary of nearly 80-100, and completed an educational course on dental assistance. Nearly one-third of the participants reported high satisfaction with their job, and less than 10% of them were satisfied with their salary. The assistants had adequate knowledge about most aspects of infection control. Nearly 40% of them reported no education on infection control, and 35-45% declared that they usually sterilized dental rotary instruments using disinfectants, but not autoclaving. Almost 60% of the assistants reported complete vaccination before entering their job. Conclusion Dental assistants in Iran are rather young, highly educated women with a relatively high workload, but low job satisfaction. Their professional knowledge and performance were deficient in some aspects, reflecting inadequacies in their education. Delivery of efficient dental services with high standards requires qualified dental personnel with formal academic education based on an efficient credentialing system.